Current Techniques of Water Solubility Improvement for Antioxidant Compounds and Their Correlation with Its Activity: Molecular Pharmaceutics - Arif Budiman; Agus Rusdin; Diah Lia Aulifa (MDPI AG, 2023)
The aqueous solubility of a drug is important in the oral formulation because the drug can be absorbed from intestinal sites after being dissolved in the gastrointestinal fluid, leading to its bioavailability. Almost 80% of active pharmaceutical ingredients are poorly water-soluble, including antioxidant compounds. This makes antioxidant activity inefficient in preventing disease, particularly for orally administered formulations. Although several investigations have been carried out to improve the solubility of antioxidant compounds, there is still limited research fully discussing the subject. Therefore, this study aimed to provide an overview and discussion of the issues related to the methods that have been used to improve the solubility and activity of antioxidant compounds. Articles were found using the keywords "antioxidant" and "water solubility improvement" in the Scopus, PubMed, and Google Scholar databases. The selected articles were published within the last five years to ensure all information was up-to-date with the same objectives. The most popular methods of the strategies employed were solid dispersion, co-amorphous, and nanoparticle drug delivery systems, which were used to enhance the solubility of antioxidant compounds. These investigations produced impressive results, with a detailed discussion of the mechanism of improvement in the solubility and antioxidant activity of the compounds developed. This review shows that the strategies used to increase the solubility of antioxidant compounds successfully improved their antioxidant activity with enhanced free radical scavenging abilities.